Особливості впливу природно-географічних чинників на формування системи розселення Закарпатської області - Качайло, Михайло; Kachailo, Mykhailo (My University, 2017)
У статті досліджено природно-географічні чинники формування системи розселення Закарпатської області; проаналізовано їх вплив на формування територіальної системи розселення області, виділено сприятливі чинники природи, які позитивно впливають на формування системи розселення Закарпатської області: сприятливий помірний клімат формування поселенської мережі рівнинної та передгірної частин області, густа гідрографічна мережа, високий рівень забезпеченості водними ресурсами на одну особу, значні запаси лісових ресурсів, висока забезпеченість природними рекреаційними ресурсами. Проаналізовано та виокремлено фактори, які негативно впливають на формування системи розселення області: переважно гірський рельєф території області, сейсмічна активність Карпатських гір, невисока родючість ґрунтів в області, низький рівень забезпечення мінеральними ресурсами, низька забезпеченість земельними ресурсами на одну особу. The article examines the natural and geographical factors of the formation of settlement system of Transcarpathian region; also their influence on the formation of territorial settlement system is analyzed and favourable environmental factors which positively effect on the formation of settlement system of Transcarpathian region are provided. These factors a favorable temperate climate for the formation of the settlement network of the plains and foothills of the region, dense hydrographical network, high availability of water resources per capita, sufficient reserves of forest resources, high availability of natural recreational resources. The factors which negatively effect on the settlement system of Transcarpathian region are analyzed and highlighted. They are the following: mainly the mountainous relief of the region, seismic activity of the Carpathian Mountains, poor soil fertility in the area, low level of mineral resources and low provision of land resources per person.
Features of Influence of Natural and Geographical Factors on the Formation of the Settlement Systems of Transcarpathian Region
Keywords: система розселення; природні умови; природні ресурси; рельєф; клімат; гідрографічна мережа; settlement system; environmental conditions; natural resources; relief; climate; hydrographical network